Microbial Iron Reduction by Enrichment Cultures Isolated from Estuarine Sediments - Tugel, Joyce B. (1986)
Microbial Fe reduction in acetate- and succinate-containing enrichment cultures initiated with an estuarine sediment inoculum was studied. Fe reduction was unaffected when SO(4)(2−) reduction was inhibited by MoO(4)(2−), indicating that both processes could occur independently. Bacterially produced sulfide precipitated as FeS but was not completely responsible for Fe reduction. The separation of oxidized Fe particles from bacteria by dialysis tubing demonstrated that direct bacterial contact was necessary for Fe reduction. Fe reduction in cultures amended with NO(3)(−) was delayed until NO(3)(−) and NO(2)(−) were removed. However, bacterial attachment to oxidized Fe particles in NO(3)(−)-amended cultures occurred early during growth in a manner similar to NO(3)(−)-free cultures. During late stages of growth, bacteria not attached to Fe particles became pale and swollen, while attached cells remained bright blue when examined by 4′,6-diamidine-2-phenylindole epifluo-rescence microscopy. The presence of added oxidized Mn had no effect on Fe reduction. The results suggested that enzymatic Fe reduction was responsible for reducing Fe in these cultures even in the presence of sulfide and that cells incapable of Fe reduction became unhealthy when Fe(III) was the only available electron acceptor.